PENERAPAN MANHAJ TERHADAP PENGUATAN FIKIH KADERISASI ULAMA PONDOK PESANTREN AS’ADIYAH SENGKANG - Muchsin, Agus (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper discusses about the tradition of fiqh Madzhab in manhaji in scholars regeneration at Islamic boarding schools As’adiyah Sengkang. The focus of the study is the fiqh construction of Ma’had al-Aliy and implementation of Ma'had al-Qaeda Usuliyah in strengthening fiqh Ma’had al-'Aliy at Islamic boarding schools As’adiyah Sengkang. The approach of this study is a qualitative descriptive approach. It is concluded that the fiqh construction of Islamic boarding school As'adiyah is determined by scholars because they have full authority to lead and to determine the reference books of jurisprudence at the school. Then, the application of the methodology of fiqh can be seen in the use of the rules: (1) fiqhiyah; al-Umuru bi maqashidiha regard to the intention of ablution, (2) lughawiyah; in terms of mulamasah and permissibility mengqashar and shorten pray only for those on trip by using using Zahir meaning, not Majazi, and (3) ushuliyah in the distribution of tithes to eight asnaf.